Evaluation of railway versus highway emissions using LCA approach between the two cities of Middle Anatolia - Bilgili, Levent; Kuzu, S. Levent; Cetinkaya, Afsin Y.; Kumar, Prashant (ELSEVIER, 2019)
Transfer of people and transportation of goods is an indispensable part of our daily lives. Choosing the most environmentally friendly alternative will have the least impact on human health, ecosystem, and the materials. This study aims to carry out a comparative assessment of various emission scenarios from highway and railway transportation between Kirsehir and Nigde-Ulukisla in the middle Anatolian Peninsula, in Turkey, to allow making an optimum decision from an environmental viewpoint. Currently, the transportation is sustained through highway, which has 232.6 km length between the cities used as a case study. High-speed railway construction is projected on the same route. We formed different capacity alternatives as alternative scenarios and life cycle assessment approach was applied to these scenarios. Environmental damage ratio decreased with the increasing utilization ratio of the railway. The greatest change was seen in ecosystem quality. We also assessed emissions during the construction activities of both railway and highway. A social cost-benefit analysis suggested that damage cost in the current situation was (sic)562,000. The scenario with 100% replacement of highway with railway transportation showed the lowest damage cost ((sic)157,000) while the highest damage cost was due to NOx emissions.
Keywords: Life cycle assessment; Sustainability; Social cost-benefit analysis; Transportation; Emissions; LIFE-CYCLE ASSESSMENT; PASSENGER TRANSPORT; AIR-POLLUTION; CONSTRUCTION; CARBON; REDUCTION; PARTICLES; QUALITY; IMPACT; Construction & Building Technology; Science & Technology - Other Topics; Energy & Fuels